Evaluation of Human Attachment by Larval Amblyomma maculatum (Acari: Ixodidae) - Portugal, José Santos; Goddard, Jerome (Journal of medical entomology, 2016)
The tick, Amblyomma maculatum Koch (Gulf Coast tick), has recently been shown to be an important disease vector of both medical and veterinary concern. Although much is known about the behavior and ecology of adults, little is known of the immatures. Larval feeding on humans has never been demonstrated (and thus, there are no collection records from humans). In this experiment, 10 larval A. maculatum, Amblyomma americanum (L.) (a positive control), and Dermacentor variabilis (Say) (a negative control), were applied to both forearms of 10 human volunteers (five male, five female). Ticks were placed in plastic caps and secured to skin with medical-grade adhesive tape, and volunteers remained sedentary during the experiment. After 15 min, caps were removed, and attachment was determined using fine-tipped forceps. Any A. maculatum that were attached were then removed and subsequently examined microscopically to verify identification. In total, 34 ticks attached to the subjects, including 11 A. maculatum (5.5%), 23 A. americanum (11.5%), and no D. variabilis. Amblyomma maculatum attached to six volunteers, and no apparent association between gender and attachment rate was noted. No skin lesions developed in the human volunteers bit by A. maculatum. This is the first report of larval A. maculatum attaching to humans, and is significant in that Rickettsia parkeri, a human pathogen vectored by this species, has recently been reported to be transmitted transovarially. If A. maculatum are infected as larvae, they could potentially transmit R. parkeri to people.